A carbon nanomaterial derived from a nanoscale covalent organic framework for photothermal therapy in the NIR-II biowindow. Issue 56 (17th June 2020) - Guan, Qun; Zhou, Le-Le; Zhou, Li-Na; Li, Mengdi; Qin, Guo-Xin; Li, Wen-Yan; Li, Yan-An; Dong, Yu-Bin
Abstract : A nanoscale carbon nanomaterial was synthesized through pyrolysis of its NCOF precursor, and the obtained carbon nanoparticles (CNPs) can be highly efficient NIR-II photothermal agents for antitumor treatment via PTT. Abstract : Herein, we report a microporous carbon nanomaterial that was generated from a nanoscale covalent organic framework precursor via a simple pyrolysis approach. The obtained carbon-based nanoparticles possessed a broad NIR absorption capacity and exhibited a high level of photothermal conversion ability ( η = 50.6%) in the NIR-II biowindow. Its excellent PTT antitumor efficiency was fully evidenced by in vitro and in vivo experiments under 1064 nm laser irradiation.